Research of indexes of physical development, physical preparedness and functional state of students aged 10-11 years under the influence of engagement in rugby-5 - Filenko L.V; Filenko I.U; Martirosyan A.A (Kharkov National Pedagogical University, 2013)
Height, weight, speed, adroitness, force and speed-power internalss, is investigated, indexes of the functional state of the cardiovascular system of students aged 10-11 years which taking the lessons of physical culture of rugby-5. In research took part 52 students of 5th forms of the Kharkiv gymnasium 172. Expediency of the use of rugby-5 engagement physical culture at secondary school is grounded. The basic indexes of physical preparedness of schoolchildren of 10-11 years are considered. Dependence of indexes of physical development is established, physical preparedness and functional state of the cardiovascular system of organism of pupils under impact of taking up rugby-5. We prove the equivalence game Rugby-5 from other sports included in the school curriculum and adaptability of the sport to the physical performance of students aged 10-12 years.